Algorithmic memorial videos: Contextualising automated curation. (April 2018) - Lambert, Alex; Nansen, Bjorn; Arnold, Michael
Web platforms such as Facebook and Google have recently developed features which algorithmically curate digital artefacts composed of posts taken from personal online archives. While these artefacts ask people to fondly remember their digital histories, they can cause controversy when they depict recently deceased loved ones. We explore these controversies by situating algorithmic curation within the media ethics of grief, mourning and commemoration. In the vein of media archaeology, we compare these algorithms to similar work done by skilled professionals using older media forms, drawing on interviews with Australian funeral slideshow curators. This professional commemorative labour makes up part of a broader, institutionalised system of 'death work', a concept we take from thanatology. Through the media ethics of death work, we critique the current shortcomings of algorithmic memorials and propose a way of addressing them by 'coding ethically'.